2015
DOI: 10.1159/000441011
|View full text |Cite
|
Sign up to set email alerts
|

Metformin-Derived Growth Inhibition in Renal Cell Carcinoma Depends on miR-21-Mediated <b><i>PTEN</i></b> Expression

Abstract: Purpose: Metformin (MF) acts as a tumour-suppressor in renal cell carcinoma (RCC) by inhibiting the AKT/mTOR pathway via AMPK activation. Here, we explore the influence of miR-21 and its target gene PTEN on MF effects in CAKI-1 and CAKI-2 cells. Methods: Proliferation assays (MTS) and qRT-PCR after transient transfection with pre- and anti-miR-21 and MF treatment were conducted. AMPK-dependency was assessed via transfection of siAMPK. The expression of PTEN, AKT and miR-21 after transient pre-miR-21 transfecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…MiR-21 is highly expressed in multiple cancers, such as epithelial cell cancer, connective tissue cancer, hematopoietic cell cancer, reproductive cell cancer and nerve cell cancer [9]. Previous studies have demonstrated that the target genes of miR-21 including phosphatase and tensin homolog detected on chromosome 10 (PTEN), Bcl-2 , TPM1 and PDCD4 which are cancer suppressed genes [1013]. Previous studies have shown that miR-21 regulates PTEN by interacting with its target gene 3′-UTR and participates in the process of cancer occurrence and development [1415].…”
Section: Introductionmentioning
confidence: 99%
“…MiR-21 is highly expressed in multiple cancers, such as epithelial cell cancer, connective tissue cancer, hematopoietic cell cancer, reproductive cell cancer and nerve cell cancer [9]. Previous studies have demonstrated that the target genes of miR-21 including phosphatase and tensin homolog detected on chromosome 10 (PTEN), Bcl-2 , TPM1 and PDCD4 which are cancer suppressed genes [1013]. Previous studies have shown that miR-21 regulates PTEN by interacting with its target gene 3′-UTR and participates in the process of cancer occurrence and development [1415].…”
Section: Introductionmentioning
confidence: 99%
“…PTEN and Akt pathways were associated with miR-21-induced EMT, and past research confirmed that PTEN is an miR-21-directed target gene [64-68]. Meng et al showed that if miR-21 was inhibited, expression of its target gene PTEN would upregulate [69].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…In addition to AMPK and mTOR, metformin has been shown to affect other oncogenic signaling pathways. Li and colleagues reported that metformin suppresses the proliferation and growth of osteosarcoma and renal cell carcinoma cells by suppressing Akt phosphorylation, which was associated with increased phosphatase and tensin (PTEN) expression ( Kalogirou et al, 2016 ; Li et al, 2018 ). Besides, metformin could activate the MEK/ERK signaling pathway to promote leukemia cell differentiation and apoptosis ( Huai et al, 2012 ).…”
Section: Molecular Mechanisms Of Antineoplastic Effectsmentioning
confidence: 99%